If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x(x+19)=0
We multiply parentheses
6x^2+114x=0
a = 6; b = 114; c = 0;
Δ = b2-4ac
Δ = 1142-4·6·0
Δ = 12996
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{12996}=114x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(114)-114}{2*6}=\frac{-228}{12} =-19x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(114)+114}{2*6}=\frac{0}{12} =0
| 34x-3+39x-1=22 | | 1/4x=695 | | 6x+3+39x-4=125 | | -12+4v=5(6+5v) | | 56x-2+76x-2=40 | | 14+4p=-3(4+3p) | | (Y+6)-(5y+7)y=-2 | | -2n-14=n+4 | | 7x+18=4x+60 | | 7r+5=5+8r | | 7x-3=18x=3 | | 5x-5=-2x+7x | | 1+2n=-7+3n | | x^2+32500=76600 | | 2x-4=18x=11 | | 2j+13=4j-5 | | x^2+200x=166400 | | -6v+4(v+8)=38 | | 4(2)^(-4x)+2=66 | | 76-8z=2(z-2) | | 4(2)^-4x+2=66 | | p+(2+3)=10 | | -0.3x–4=9.4 | | –11=x+5 | | (7+2x)^2=11 | | 12=w12 | | t=-16t2+48t+4 | | 6v+15=2v+47 | | 3x+-1(x+-7)=18 | | x+10=-5x-4 | | 16^2+x^2=27^2 | | 22.5+2y=7y+11 |